Current Achievements in Geosite Research (Analele Universității București.Geografie, 2025)
One of the many ways of study by which geography can be useful in today's economic context is by analyzing those geographic locations that are important not only scientifically but also culturally, historically, aesthetically or economically. Called in the literature "a bridge between science and culture" (Reynard et al., 2018), geosites are the subject of recent but increasingly complex concerns within geosciences. Amid growing awareness of the importance of the human-environment relationship both for individuals and for society as a whole, the study of geography in recent decades has manifested a predisposition to focus on increasingly practical applications, and the scope of geographic research has broaden to actions that have in the forefront the highlighting of natural heritage, natural monuments and the need to preserve, protect and enhance the environment.